CAMBODIAN BUDDHIST MONKS’ MOTIVATION IN LEARNING ENGLISH: GRADE LEVEL ANALYSIS - Sophea Phann; Sereyrath Em; Sopheng Tep (IKIP Siliwangi, 2023)
English is the world language. Most countries in the world including Cambodia have adopted this language into their school curriculum. Thus, learning English has become an essential need for many people in Cambodia and the world. There are many factors contributing to the success of English language education. One of the most important components is motivation. There are two types of motivation including intrinsic and extrinsic ones. The present study employed a quantitative design and aimed to examine if there were statistically significant differences among Cambodian Buddhist monk students’ motivation in learning English. 93 Cambodian Buddhist monk students learning at a Cambodian Buddhist primary school participated in the study. The results show that there were statistically significant differences in students’ motivation from different grades. Finally, a study with a larger sample size is recommended. A qualitative study to explore students’ motivation in learning English is also recommended.